Improving Plan-Based Interactive Narrative Generation - Robertson, Justus (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2013)
I am interested in algorithms that generate well structured interactive narratives that allow human participants to effect change in a story world. Narrative can be structured as a sequence of actions to be carried out by a set of characters in a particular environment. This narrative structure can be generated by AI planning. A process called accommodative mediation may be used on a single narrative plan to create a participatory experience that branches based on a human’s interactions as a character within the story. However, accommodation is limited by search time and the number of plans the algorithm can possibly reach. In this paper, I discuss an initial modification of accommodative mediation that expands the space of plans the algorithm may search. I also identify several avenues by which the process may continue to be improved.